Basic analysis of facial ageing: The relationship between the superficial musculoaponeurotic system and age. (30th January 2019) - Okuda, Itsuko; Yoshioka, Naoki; Shirakabe, Yukio; Akita, Keiichi
Abstract: Background: The superficial musculoaponeurotic system (SMAS) is an anatomical structure involved in the facial ageing process. We aimed to evaluate the SMAS laxity using multi‐detector row computed tomography (MDCT) as a diagnostic tool, and to analyse the relationship between SMAS laxity and age. Methods: Fifty‐seven female subjects (aged 21‐57 years) were enrolled in the study. The subjects were divided into two age groups: one below the mean age (Group Y, 30 subjects) and one over it (Group O, 27 subjects). The Posture Change (PC)‐induced SMAS Laxity Index was measured using reconstructed CT images, and the relationship between the PC‐induced SMAS Laxity Index and age was analysed. Results: The PC‐induced SMAS Laxity Index was significantly larger in Group O than in Group Y. As well, a strong and significant positive correlation was detected between the PC‐induced SMAS Laxity Index and age ( r = 0.72; P < 0.001). Conclusions: The use of MDCT provides insight into the detailed changes associated with ageing that take place within the cheeks. This study objectively demonstrated that SMAS laxity and age are factors associated with facial ageing, as the SMAS laxity increased with age. Finally, the imaging features confirmed the dermatological and aesthetic knowledge gained from plastic surgery regarding the loss of the SMAS supporting force due to facial ageing.